Characterization and utilization of pulp and paper mill sludge digesting thermophilic bacteria in composting process - Chau, Ngo Thi Tuong; Thien, Le Van; Lan, Pham Thi Ngoc; Futamata, Hiroyuki (Penerbit Universiti Kebangsaan Malaysia, 2018)
Pulp and paper mill sludge (PPMS) was found to be poorly colonised with thermophilic microorganisms. However, evidence to support the need for inoculation to facilitate PPMS composting has only been demonstrated in one instance. In this study, we aimed to: screen and identify PPMS digesting thermophilic bacterial strains; investigate effects of the mixture of selected thermophilic bacterial strains on PPMS digestion; and utilize this mixture as start inoculum in PPMS composting and assess the quality of compost product. The results showed that eleven thermophilic bacterial strains were isolated from Bai Bang PPMS by the enrichment culture method. Among these, three strains which reflected high growth rates on the plates of Minimal Media Agar supplemented with Bai Bang PPMS and showed hydrolytic and ligninolytic activities on the agar plates containing appropriate inductive substrates were selected. Based on the morphological, biochemical characteristics and 16S rRNA gene sequencing, they were identified as Bacillus subtilis. The inoculation with the mixture of selected strains enhanced remarkably Bai Bang PPMS digestion. The dry weight decrease, volatile suspended solids removal, dehydrogenase and protease activities in the inoculated sludge were 2.1-, 1.5-, 1.3- and 1.2- fold higher, respectively, compared to the non-inoculated sludge. The assessment of compost quality based on stability using the alkaline trap method and maturity using the germination and root elongation test showed that the inoculated compost was stable and mature while the non-inoculated compost was unstable and immature. These thermophilic bacterial strains therefore have great potential for Bai Bang PPMS composting.